Clinical transplantation using negative pressure ventilation ex situ lung perfusion with extended criteria donor lungs - Max T. Buchko (Nature Portfolio, 2020)
Preclinical studies have shown that negative pressure ventilation ex situ lung perfusion results in less ventilator-induced lung injury compared to positive pressure ventilation of donor lungs during transplantation procedures. Here the authors perform a single-arm clinical trial with 12 participants to study patient survival and primary graft dysfunction with ex situ lung perfusion.